Numerical taxonomic study of the genus Crotalaria L. (Crotalarieae, Fabaceae) in Nigeria - Yaradua, Samaila Samaila; Alzahrani, Dhafer Ahmed; Bello, Abubakar (Biodiversity: Research and Conservation, 2018)
Numerical taxonomic study of the genus Crotalaria L. in Nigeria was conducted to identify and differentiate some of the species of the genus Crotalaria using numerical taxonomy based on quantitative and qualitative characters. Field work was conducted, where different species were collected and analyzed using multivariate analysis. The results showed that all the collected species are distinct at Euclidian distance of 0.41 in the cluster analysis with Cophenetic correlation (r)=0.964. The ordination analysis based on the results of the PCA, separated the specimens into 7 groups corresponding to the result of cluster analysis. The first two components of the PCA account for 81.5%. The length of petiole, width of leaflet and length of fruit contributed more to showing delimitation among the species.